Decentralization and welfare: theory and an empirical analysis using Philippine data (Public Sector Economics - submission site, 2021)
This study theoretically and empirically analyzes the relationship between decentralization and welfare. The model identifies conditions in which a decentralized government is utility-maximizing compared to a centralized one. The empirical analysis utilized data from Philippine provinces to study the relationship between several decentralization indicators and welfare, as measured by per capita income, human development index, and poverty. Results suggest that fiscal independence, or the ability of local governments to generate their own revenues to finance their own expenditures rather than relying on central government transfers, is positively associated with per capita income and HDI. Moreover, this relationship is stronger when governance is better and weaker among lower-income provinces. In contrast, a higher number of local government units per population is linked to adverse development outcomes, and this association is stronger among lower-income provinces and weaker among those with good governance.